Persecutory delusions and psychological well-being - Freeman, D; Startup, H; Dunn, G; Wingham, G; Černis, E; Evans, N; Lister, R; Pugh, K; Cordwell, J; Kingdon, D (Dr. Dietrich Steinkopff Verlag GmbH and Co. KG, 2014)
Purpose: Persecutory delusions are one of the key problems seen in psychotic conditions. The aim of the study was to assess for the first time the levels of psychological well-being specifically in patients with current persecutory delusions. Method: One hundred and fifty patients with persecutory delusions in the context of a diagnosis of non-affective psychosis, and 346 non-clinical individuals, completed the Warwick-Edinburgh Mental Well-Being Scale and symptom assessments. Results: Well-being scores were much lower in the persecutory delusions group compared with the non-clinical control group. 47 % of the persecutory delusions group scored lower than two standard deviations below the control group mean score. Within the patient group, psychological well-being was negatively associated with depression, anxiety, and hallucinations. In both groups, lower levels of well-being were associated with more severe paranoia. Conclusions: Levels of psychological well-being in patients with current persecutory delusions are strikingly low. This is likely to arise from the presence of affective symptoms and psychotic experiences. Measurement of treatment change in positive mental health for patients with psychosis is recommended. © 2013 Springer-Verlag Berlin Heidelberg.